Oral Manifestations in Hemodialysis Patients and Their Knowledge and Attitude Towards Oral Health - Mainali, Apeksha; Chettri, PK (Nepal Medical College Journal, 2020)
Oral cavity is the mirror of systemic health. Amongst various systemic diseases, Chronic Kidney Disease (CKD) is one such disease that presents with a spectrum of oral manifestations. The oral health care professionals need to attain a holistic approach to the management of patients with complex medical problems and should be in par with the changing technology and medical advances. Amongst all the systemic disorders, diseases of the renal system pose a major cause of morbidity and mortality worldwide, as the kidneys are vital organs for maintaining a stable internal environment. The plethora of oral manifestations observed in chronic renal failure and associated therapies are altered taste, gingival enlargement, xerostomia, various mucosal lesions like hairy leukoplakia, lichenoid reactions, ulcerations, angular chelitis, candidiasis etc. With growing awareness about the inter-relationship between dental and medical problems, the role of dentist has become pivotal in overall health care of patients with CKD and also to render services for the oral findings of such diseases. This information can be used for designing effective intervention strategies to prevent and manage oral manifestations in adult hemodialysis patients of Nepal. The objective of this cross sectional study was to see the oral manifestations in hemodialysis patients and their Knowledge and attitude towards Oral Health. Face to face interviews was done with the patients to gather knowledge regarding socio-demographic variables and tobacco history. Following statistical analysis, it was seen that multiple oral manifestations were seen in patients undergoing hemodialysis.